Management of 57 year old morbidly obese female with multiple comorbidities with proximal humerus fracture – interscalene block: A case report - Dr.Subhashree J; Dr.Suchitra M; Dr. Krishnapriya; Dr. Vineet Reddy (International Journal of Pharmacy Research & Technology (IJPRT), 2025)
We present a case of 57 year old female, morbidly obese female patient with proximal humerus fracture posted for open reduction and internal fixation. She was a known case of Diabetes mellitus, hypertension, chronic kidney disease on thrice weekly hemodialysis and on home oxygen therapy. She had the fracture on the same side of AV fistula. Her BMI was 42.5 and she was not able to lie down supine. She underwent one cycle of hemodialysis the previous night. After shifting to operation theatre, 18G intravenous cannula was secured in other limb. We positioned her in head up position with an angle of 45° and bolsters under her knees, continued oxygen through face mask at 5L/min. We anesthetized her using ultrasound and peripheral nerve stimulator guided interscalene block with 20ml of 0.5% bupivacaine. We checked for motor blockade after 20 minutes of giving the block. Procedure went uneventful and she was shifted to icu in head up position only, on the bed. This case highlights the practical difficulties like positioning, securing an iv cannula, difficult airway that we encounter with obese individual with multiple comorbidities. So we need to weigh up the risks and benefits and decide the mode of anesthesia, so as to avoid the complications.